Temporal changes in innate immunity parameters, epinecidin gene expression, and mortality in orange-spotted grouper, Epinephelus coioides experimentally infected with a fish pathogen, Vibrio harveyi JML1. Issue 69 (October 2017) - Amar, Edgar C.; Faisan, Joseph P.; Apines-Amar, Mary Jane S.; Pakingking, Rolando V.
Abstract: Changes in innate immunity parameters and epinecidin mRNA transcript levels were examined to characterize the non-specific immune response of E. coioides to pathogenic V. harveyi JML1 isolated from affected cage-cultured fish. After fish had been injected with bacteria at a dose causing 30% mortality, blood and tissue samples were collected at 0, 6, 12, 24, 48, 72, 96, 120, and 240 h post-infection (hpi) for assessment of indices such as the oxidative burst (OB) and phagocytic index (PI) of head kidney cells, and lysozyme activity (LYS) and total immunoglobulin (Total Ig) levels of the plasma. The epinecidin mRNA transcript levels (EGE) from skin, gills, liver, kidney, and spleen tissues were also determined by gel-based RT-PCR. Lastly, daily mortality (DM), liver total bacterial load (TBC), and presumptive Vibrio count (TVC) were monitored up to 240 hpi. The results revealed that bacteria proliferated rapidly in fish tissue, reaching peak densities at 24 hpi for both TBC and TVC but was on a downward trend thereafter. The pattern in fish mortality closely correlated with TBC and TVC. Total Ig, OB, and PI in E. coioides were suppressed in the early part of infection when V. harveyi load was high but recovered and later increased as bacterial density declined. LYS and EGE were consistently high and their activities were not hampered by bacterial infection. The study demonstrated that V. harveyi JML1 interacts with E. coioides by transiently inhibiting some immune parameters resulting in mortalities. However, consistently high LYS, upregulated EGE, and resurgent PI, OB and Total Ig conferred resistance and subsequent recovery in the fish. The study provides new insights on the interaction between E. coioides and V. harveyi JML1 that can aid in formulating health management strategies for groupers. Further studies on prophylactic interventions to enhance the innate immune response in grouper during infection with V. harveyi JML1 are suggested. Graphical abstract: Kinetics of bacterial growth, innate immune parameters, epinecidin gene expression, and survival in V. harveyi JML1-infected grouper. LYS, lysozyme; EGE, Epinecidin gene expression; OB, oxidative burst; PI, phagocytic index; TIg, total immunoglobulin. Highlights: A unique pattern of interaction between E. coioides and V. harveyi JML1 was found. 3 of 5 parameters were suppressed early by infection of grouper with V. harveyi JML1. 2 parameters were always high and not inhibited by V. harveyi JML1. Fish mortality increased and decreased with total bacterial load and Vibrio count. Increase of all parameters in the later part of infection coincided with disease recovery.